Nanofabrication: General Programmable Growth of Hybrid Core–Shell Nanostructures with Liquid Metal Nanodroplets (Adv. Mater. 11/2021). Issue 11 (16th March 2021) - Ren, Long; Cheng, Ningyan; Man, Xingkun; Qi, Dongchen; Liu, Yundan; Xu, Guobao; Cui, Dandan; Liu, Nana; Zhong, Jianxin; Peleckis, Germanas; Xu, Xun; Dou, Shi Xue; et al.
Abstract : In article number 2008024, Long Ren, Yi Du, and co‐workers report a general programmable strategy to fabricate core–shell nanostructures by using liquid‐metal nanodroplets as reformable core templates, offering general use in producing nanostructures with multiple, complex, and desired structures, compositions, and sizes on a large scale. The established design rules for making polyelemental core–shell systems in desired chemistry are expected to result in multifunctional materials for varying applications.